Heritage conservation for city marketing: The imaging of the historic city of Georgetown, Penang - Ismail, S.; Yahaya, A.; Hamzah, H. (Faculty of Built Environment, University of Malaya, 2008)
The process of imaging for city marketing purposes has the implication on culture, conservation and heritage. City marketing, especially in the European context, has been examined in interdiscip linary literature with special focus on imaging for tourism. Little is reported about the imaging of those cities' ex-colonies in the East. The Historic City of Georgetown in Penang, dubbed 'the City of Living Culture', has been gearing her development towa rds living up to the image. This paper examines the imaging of the Historic City of Georgetown for heritage tou rism and city marketing tool by the public agencies involved. A short introduction to city marketing, imaging and heritage tourism is offered due to sparse literature in the built environment literature and to serve as a foundation to the main discourse of this paper. The bulk of this paper discusses the conservation of heritage as image dimensions in the marketing of Georgetown. We submitted that Georgetown has successfully utilised and capitalised on its cultural diversity and tangible heritage based on its colonial legacy to promote the city as evidenced by its recent inscription into UNESCO's World Heritage Site list. Nonetheless, building and maintaining the synergy between the government, the private sector and the people is essential for the city's heritage tourism industry.